2019
DOI: 10.1177/0018578718823484
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Olanzapine in a Critically Ill Patient: An Evolving Route of Administration

Abstract: Purpose: The purpose of the article is to describe the successful use of parenteral olanzapine intravenously (IV) in a critically ill patient with severe agitated delirium. Summary: A 70-year-old man was admitted to the medical intensive care unit requiring plasmapheresis with platelet counts consistently below 20 000/µL secondary to thrombotic thrombocytopenic purpura (TTP). The patient had experienced agitated delirium requiring treatment, which was complicated by electrocardiogram (EKG) findings of a prolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Previous data in the ICU population are limited to case reports, poster abstracts, and studies involving smaller sample sizes. [5][6][7]9 The majority of patients received multiple doses of IVP olanzapine, which has not been well established in previous studies in the ICU population. 9 The inpatient population is important to analyze because most previous studies on IVP olanzapine took place in the ED setting, where repeat dosing and extended durations of therapy are uncommon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous data in the ICU population are limited to case reports, poster abstracts, and studies involving smaller sample sizes. [5][6][7]9 The majority of patients received multiple doses of IVP olanzapine, which has not been well established in previous studies in the ICU population. 9 The inpatient population is important to analyze because most previous studies on IVP olanzapine took place in the ED setting, where repeat dosing and extended durations of therapy are uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…1 Previous studies have demonstrated the off-label usage of intravenous push (IVP) olanzapine across multiple indications. 2-11 IVP olanzapine is seen as a useful option in acute agitation because it can be given rapidly in patients with IV access. 3-9 Further rationale for the off-label usage of IVP olanzapine is the thought of a faster onset of action compared with the IM route of administration, which can take up to 45 minutes to reach peak concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…QTcB 421 and QTcF 423 ms while off galantamine increased to 503 and 477 ms, respectively, after reinitiating treatment. QTcB 443 and QTcF 452 ms after discontinuing galantamine and irbesartan Olanzapine Lorenzo et al 2020 99 70 Male Agitated delirium while hospitalized Tamsulosin, terazosin, ibuprofen QTc 447 ms on admission, increased to 485 ms during hospitalization and treatment with haloperidol, ziprasidone, lorazepam, diazepam, and/or dexmedetomidine. QTc normalized after switching to olanzapine IV 2.5–5 mg every 4 hr Jeon et al 2011 97 42 Female Psychosis Olanzapine 2.5 mg/d, warfarin 3 mg/d, diazepam 4 mg/d, valproic acid 300 mg BID, topiramate 100 mg BID QTc 591 ms on admission with dysrhythmia and intermittent TdP in a patient with a history of open-heart surgery.…”
Section: Literature Searchmentioning
confidence: 99%
“…2 Despite lack of FDA approval, there has been an increased exploration of IV olanzapine for the management of acute agitation. 3-8 It is suggested that olanzapine may pose a better safety profile compared to IV haloperidol, including fewer extrapyramidal side effects and a lower risk of QTc prolongation and torsades de pointes (TdP). 9 Furthermore, the use of haloperidol has been associated with an increased risk for neuroleptic malignant syndrome in human studies 10 and delayed recovery in neurologic injury in animal studies.…”
Section: Introductionmentioning
confidence: 99%